Bifurcations and the Emergence of L2 Syntactic Structures in a Complex Dynamic System - Evans, D. Reid; Larsen-Freeman, Diane (Frontiers in Psychology, 2020)
We report on a complex dynamic systems study of an untutored adult French learner’s development of English syntax, specifically two non-finite adverbial constructions. The study was conducted over one academic year of thirty weeks. From an analysis of L2 speech samples collected weekly, certain patterns in the flux emerged. The learner’s ensuing second language development is characterized by a series of bifurcations, stemming from forms competing for the same functional terrain. Each bifurcation is accompanied by turbulence as the system moves from one attractor state to another. The transition is characterized by loss of stability, an increase in variability, and a period of dysfluency. It is in the dynamic relationship of accuracy and fluency that novel syntactic forms emerge, both convergent with and divergent from dominant contextual patterns, with dominance established by consulting a well-known corpus of contemporary English. Non-linear development occurs with continuous and iterative exposure to and interaction in English—from relexification to adaptation and synchronization, animated by the learner’s perception and memory of regular sequential associations, to pruning of divergent forms. What results over time is a branching hierarchy, connecting online processing with over time development, much as in a fractal cladistic taxonomy. Competing forms continue to co-exist in the learner’s repertoire, which is likely more typical of adult L2 development than of L1 acquisition.